2015
DOI: 10.5114/aoms.2015.50971
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic posterior cruciate ligament reconstruction with allograft versus autograft

Abstract: IntroductionThe aim of the study was to compare and analyze retrospectively the outcomes of arthroscopic posterior cruciate ligament reconstruction with autograft versus allograft.Material and methodsSeventy-one patients who underwent arthroscopic posterior cruciate ligament reconstruction with an autograft or allograft met our inclusion criteria. There were 36 patients in the autograft group and 35 patients in the allograft group. All the patients were evaluated by physical examination and a functional ligame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 36 publications
0
29
0
1
Order By: Relevance
“…Li et al 17 randomized patients to autograft or allograft. Two studies 16,24 selected graft type based on patient preference. Kim et al 13 performed PCLR with a bone–patellar tendon–bone (BPTB) autograft except in cases of patellofemoral joint disease, patellofemoral maltracking, narrow width of the patellar tendon (<30 mm wide), or poor skin condition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al 17 randomized patients to autograft or allograft. Two studies 16,24 selected graft type based on patient preference. Kim et al 13 performed PCLR with a bone–patellar tendon–bone (BPTB) autograft except in cases of patellofemoral joint disease, patellofemoral maltracking, narrow width of the patellar tendon (<30 mm wide), or poor skin condition.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al 16 found no significant differences between groups with regard to age at surgery, BMI, or duration from injury to surgery. Sun et al 24 found no differences between groups with regard to sex, age, duration of injury (acute vs chronic), or the proportion of patients with an intraoperative finding of a meniscal injury, cartilage lesion, or medial collateral ligament (MCL) injury. Ahn et al 1 found no differences between groups with regard to age, sex, activity level, or duration from injury to surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tian et al [ 22 ] provide a meta-analysis of autograft and allografts in PCL reconstruction but include only five studies, the RCT by Li et al [ 12 ], and CCTs by Ahn et al [ 1 ], Li et al [ 11 ], Sun et al [ 21 ] and Wang et al [ 23 ], some of which we would exclude. Ahn et al [ 1 ] had only 18 patients in each group.…”
Section: Resultsmentioning
confidence: 99%
“…Six prospective studies of allografts in posterior cruciate ligament (PCL) reconstruction [ 13 15 , 20 , 26 , 27 ] were included. Two studies [ 12 , 21 ] were excluded because grafts were irradiated. There was a range of study designs, with two RCTs of allograft options, one RCT comparing allografts and autografts, two CCTs and four single-arm before and after studies.…”
Section: Resultsmentioning
confidence: 99%